Diagnostic Criteria for Vulvovaginal Infections in Pregnant Women - Ikromova Parvina Hamidjon Kizi (Journal of Science in Medicine and Life, 2024)
Vulvovaginal infections represent one of the most common problems during pregnancy. These infections can negatively affect both the mother's health and fetal development, making it crucial to promptly identify the disease and take necessary treatment measures. Diagnosing vulvovaginal infections in pregnant women has its specific features, considering the limitations in using certain treatment methods and the need to minimize risks to the fetus.